EVOLUSI TEORI FRAUD DAN RELEVANSINYA TERHADAP STRATEGI PENCEGAHAN KORUPSI DANA DESA - Fauziah, Satya (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2024)
The purpose of this research is to review the evolution of fraud theory and to describe the relationship between the evolution of fraud theory and the formulation and implementation of strategies for preventing village fund corruption. This study uses a qualitative research method with a literature review approach from various references related to the topic being studied. The evolution of fraud theory began with the discovery of the concept of white-collar crime. From this concept, fraud theory first emerged in 1953 and has continued to develop over time until 2021. The fraud theories that have been discovered can be used by the District/City Inspectorate to formulate and implement strategies for preventing village fund corruption so that the strategies applied can be more effective in preventing village fund corruption.